THE TCR 5000 CONSTANT CURRENT REGULATOR'S SAFETY DESIGN UTILIZING PROGRAMMABLE LOGISTIC CONTROL - Basil Aldrian Prawiraatmaja; arini zulfa Himayati; Annisa Baby Callista; Vania Nadhifa Azzahra (Journal of Airport Engineering Technology (JAET), 2023)
Air transportation must have security procedures from landing to taking off the plane in the application of the plane guided by the Airfield Lighting System (ALS). CCR type 5000 is one of them to provide visible information on the aircraft. At Husein Sastranegara Airport, damage often occurs on the module due to a poor grounding system and non-standard insulation resistance. This research aims to design CCR safety with TCR 5000 type, which can be applied to Husein Sastranegara International Airport concerning regulatory standards and will be outlined in this research. This research has the following objectives: to design a safety device for the CCR with TCR 5000 type, to prevent damage to the CCR module, and to be used as a reference for airport management. This study's research and development (R&D) methodology begins with observation. According to the study's findings, the PLC-based CCR 5000-type CCR safety design can reduce damage to the CCR module. The PLC will turn off the CCR's power supply if it detects an overcurrent. The buzzer will sound to facilitate technicians' ability to determine whether the CCR type TCR 5000 is experiencing overcurrent.